Respuesta :

Answer:

[tex]x^2 + 66x -371 = 0[/tex]

Step-by-step explanation:

We have two equations:

x + y = 11                 (i)

[tex]4x^2 - 3y^2 = 8[/tex]      (ii)

Clear x in equation (i) and substitute it in equation (ii)

[tex]4x^2 -3(11-x)^2 = 8[/tex]

[tex]4x^2 -3(121 -22x +x^2) = 8[/tex]

[tex]4x^2 -363 + 66x - 3x^2 -8 = 0[/tex]

[tex]x^2 + 66x -371 = 0[/tex]

To find the roots of this equation we use the quadratic formula

[tex]\frac{-b +/- \sqrt{b^2 - 4ac}}{2a}[/tex]

Where:

b = 66

a = 1

c = -371

Then:

[tex]\frac{-66 + \sqrt{66^2 - 4(1)(-371)}}{2(1)}\\\\and\\\\\frac{-66 - \sqrt{66^2 - 4(1)(-371)}}{2(1)}[/tex]

Then the solutions are:

[tex]x = -33 + 2\sqrt{365} = 5.21[/tex]

and

[tex]x = -33 - 2\sqrt{365} = -71.21[/tex]

Finaly, equation could be used to solve the system is [tex]x^2 + 66x -371 = 0[/tex]